Analysis of the Factors Affecting the Income of Lontar Leaf Stitching Home Industries in Sibetan Village, Karangasem Regency - I Gusti Ayu Muni Sri Cahyanti; Ni Nyoman Yuliarmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The lontar leaf stitching home industry is a micro-enterprise that produces various types of crafts made from lontar leaves, commonly used in traditional and religious ceremonies. This industry plays a significant role in the local economy and cultural preservation. The objectives of this study are: (1) to analyze the simultaneous effect of capital, raw materials, working hours, and business duration on the income of lontar leaf stitching home industries in Sibetan Village, Karangasem Regency; and (2) to analyze the partial effect of capital, raw materials, working hours, and business duration on the income of these industries. The population of the study consists of all 50 lontar leaf stitching home industries in Sibetan Village. A saturated sampling technique was used, meaning the entire population was taken as the sample. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results show that capital, raw materials, working hours, and business duration simultaneously have a significant effect on income, accounting for 96.8 percent of the variance. Partially, each of these variables also has a positive and significant effect on income. It is recommended that artisans manage their capital efficiently—including utilizing financing from village credit institutions (LPDs)—select quality raw materials, optimize working hours, and leverage business experience through support from village-owned enterprises (BUMDes) to expand marketing and increase income.